Design and implementation of an efficient hybrid dynamic and static typing language†. (6th October 2014) - Garcia, Miguel; Ortin, Francisco; Quiroga, Jose
Summary: Dynamic languages are suitable for developing specific applications where runtime adaptability is an important issue. On the contrary, statically typed languages commonly provide better compile‐time type error detection and more opportunities for compiler optimizations. Because both approaches offer different benefits, there exist programming languages that support hybrid dynamic and static typing. However, the existing hybrid typing languages commonly do not gather type information of dynamic references at compile time, missing opportunities for improving compile‐time error detection and runtime performance. Therefore, we propose some design principles to implement hybrid typing languages that continue gathering type information of dynamically typed references. This type information is used to perform compile‐time type checking of the dynamically typed code and improve its runtime performance. As an example, we have implemented a hybrid typing language following the proposed design principles. We have evaluated the runtime performance and memory consumption of the generated code. The average performance of the dynamic and hybrid typing code is at least 2.53× and 4.51× better than the related approaches for the same platform, consuming less memory resources. Copyright © 2014 John Wiley & Sons, Ltd.